Approximate Estimation of Stability of Homogeneous Beam on Elastic Foundation - WSTAWSKA, Iwona Małgorzata; MAGNUCKI, Krzysztof; KĘDZIA, Piotr (Engineering Transactions, 2019)
The paper deals with a proposition of obtaining an analytical solution for a beam on elastic foundation. The main objective of presented work was stability analysis of the axially compressed beam. The analytical model was proposed. Shape function for inhomogeneous properties of the foundation was assumed. The Galerkin method was used to calculate the values of critical forces. Main conditions have been defined. The critical loads as a function of geometric and mechanical properties of the beam as well as inhomogeneous properties of the elastic foundation have been calculated.